Dysphagia in patients with cerebrovascular disease. Update. - Amarilis Barbié Rubiera; Ligia María Marcos Plasencia; Yolanda Aguilera Martínez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
An important number of patients with cerebrovascular disease also present dysphagia as a result of damage in cerebral hemispheres or brainstem, which contributes to negative morbility and functional rehabilitation prognosis due to the complications liked with this condition. It is a significant cause of nutritional dysfunctions, including increased in-hospital undernourishment, increased per patient expenditure and longer in-hospital stay. One of the objectives of the Nutritional Support Team of the Neuroscience and Neurology Institute is to reduce undernourishment causes in patients with neurological diseases. A wide review of the subject was performed including experts´ opinions, from the above mentioned institutions, in order to gather an updated report related with the significance of early diagnosis of dysphagia in patients with ictus and the opportune and correct use of therapeutic measures to reduce complication risk.